Aplikasi Peminjaman Buku Pada Perpustakaan Sma Nur Hasanah Kota Medan Berbasis Website - Putra, Bayu Edriansyah (Jurnal Nasional Teknologi Komputer, 2023)
The library is a gathering place for knowledge that is printed or recorded and can meet user needs in various ways, but the Library at NUR HASANAH High School in Medan City is currently still using the manual method to record students or students who want to borrow books. Therefore, for borrowing books from the SMA NUR HASANAH Library, Medan City, a website-based application will be made to make it easier and speed up the performance of library staff. By using today's sophisticated technology, it can be concluded that there will be no more queues when collecting data for book loans. The method in developing this system uses Design Thinking. As well as in making this website using the programming language PHP, CSS, Native, Database.